Indole-3 Acetic Acid Producing Rhizobacteria and its Potential to Enhance Growth of Sweetpotato (Ipomoea Batatas L.) - Maira, Lusi (2000)
The problem in sweetpotato cultivation is yield reduction with continuous planting, which can be attributed to several factors such as soil degradation, pathogenic effects, and allelopathic effects. One of the approaches to alleviate this problem is by inoculating plants with indole-3-acetic acid (IAA) producing rhizobacteria to enhance growth of sweetpotato. The study consisted of four experiments. Experiment I was the isolation of rhizobacterial strains from sweet potato rhizosphere and their performance in sweetpotato root exudate culture. Experiment II was the selection of IAA producing rhizobacteria and their effects on sweet potato growth. Experiment III was the determination of the effect of pH and carbon sources on growth of rhizobacteria isolated from sweetpotato rhizosphere. Experiment IV was the determination of the effects of L-tryptophan (T RP) on performance of IAA producing rhizobacteria on growth of sweetpotato. From the isolation procedures, 115 rhizobacterial isolates were collected from different varieties of sweetpotato grown on different soils. They were grouped into 6 types according to colour of the colonies which consist of purple, milky white, translucent, orange, yellow and brown. The study showed that 48 isolates (41.74 %) were able to grow on medium containing sweetpotato root exudate of which, 18 isolates (37.5%) were able to produce IAA in culture medium which ranged between 4 to 8 ug/m L. The first pot experiment showed that 6 isolates ( SP R 66, SP R 83, SP R 85, SP R 88, SP R 100 and 90-166) were able to stimulate the initial growth of sweetpotato vines. Three of the isolates namely SP R 66, SP R 83 and SP R 100 showed positive responses on media with wide range of pH and different carbon sources. The optimum pH of medium for rhizobacterial growth was 6.75, and the most favourable carbon source was malic acid. The second pot experiment showed that isolate SP R 66 increased the shoot dry weight, chlorophyll content and total leaf area of shoots, while isolate SP R 100 increased the dry weight and volume of roots, the storage root formation, nutrient concentration in shoots and soil nutrient contents. The addition of L-T RP to all selected rhizobacterial isolates enhanced growth and yield of sweetpotato. It related to the improved of soil chemical properties and microbial activity.